Automatic Watering of Red Ginger Plants Based on Telegram Using ESP8266 Nodemcu - Humairoh Ratu Ayu; Dwina Nurizky Syahputri; Arif Surtono; Gurum Ahmad Pauzi; Amir Supriyanto (Lambung Mangkurat University Press, 2023)
The design of an automatic watering tool for telegram-based red ginger plants has been realized using nodemcu esp8266. This study aims to create an automatic plant watering system using the YL-69 sensor and monitor the water supply in the reservoir using an ultrasonic sensor that can be monitored using Telegram application. This tool is assembled with various components such as nodemcu ESP8266 as a microcontroller, YL-69 sensor to detect soil moisture, ultrasonic sensor functions as a water level detector, water pump, and 16×2 LCD. The system works when the sensor reads soil moisture in red ginger plants> 60% then the pump turns off and if <60% then the pump turns on. Based on the results of the study, the tool can run well as indicated by the average accuracy of the YL-69 sensor of 98.61% and the water pump can turn on and off according to soil moisture conditions. In addition, the Telegram application can control and monitor watering either manually with the command /Humidity to check soil moisture, /Distance to monitor the water level in the reservoir, /PumpON to turn on the pump, /PumpOFF to turn off the pump or automatically